A wear-resistant and antibacterial TPE composite material and its application in yoga mats

By esterifying citronellol with maleic chloride and preparing citronella carbon nanotubes, combined with thermoplastic polyurethane elastomers for blending, the poor antibacterial performance and resistance of thermoplastic polyurethane elastomers in yoga mat applications are solved. The problem of insufficient wear performance has achieved excellent antibacterial, wear resistance and self-healing performance of TPE composite materials.

CN119019836BActive Publication Date: 2025-02-14ANHUI GUANTANG RUBBER & PLASTIC PROD CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411497173.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-14
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

Existing thermoplastic polyurethane elastomers have problems with poor antibacterial performance and insufficient wear resistance in yoga mat applications.

Method used

The wear-resistant and antibacterial TPE composite material was prepared by esterification of citronellol and maleic chloride, and a series of reactions were obtained by obtaining citronellol-based carbon nanotubes, and blending them with thermoplastic polyurethane elastomer.

Benefits of technology

It improves the antibacterial and wear resistance of TPE composites, and enhances its self-repairing properties, allowing it to show excellent performance in applications such as yoga mats.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_5
    Figure SMS_5
  • Figure SMS_6
    Figure SMS_6
  • Figure SMS_7
    Figure SMS_7
Patent Text Reader

Abstract

The present invention relates to the technical field of TPE composite materials, and discloses a wear-resistant and antibacterial TPE composite material and its application in a yoga mat. The present invention uses maleic acid, thionyl chloride, citronellol, furanylamine, acidified carbon nanotubes, etc. as raw materials, and obtains citronella-based carbon nanotubes through acyl chloride reaction, esterification reaction, Diels-Alder reaction, and amidation reaction, and then melt blends, granulates, and injection molds it with a thermoplastic polyurethane elastomer to obtain a wear-resistant and antibacterial TPE composite material. The thermoplastic polyurethane elastomer prepared by the present invention has excellent antibacterial properties, wear resistance, and self-repairing properties after experiments. The wear-resistant and antibacterial TPE composite material prepared by the present invention has a very important application value in a yoga mat.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of TPE composite materials, in particular to a wear-resistant and antibacterial TPE composite material and application thereof in a yoga mat. Background Art

[0002] Thermoplastic elastomer (TPE) is a blend of rubber and plastic with thermoplasticity and elasticity. It can produce plastic flow at high temperature and show high elasticity of rubber at room temperature, so it is also called the third generation of rubber. TPE can be mainly divided into rubber blended thermoplastic elastomer and chemically synthesized thermoplastic elastomer. For blended TPE, it is mainly composed of polyolefin thermoplastic elastomer and thermoplastic vulcanizate. For chemically synthesized TPE, its representative varieties mainly include thermoplastic polyurethane elastomer, thermoplastic polyester elastomer and styrene block copolymer.

[0003] Thermoplastic polyurethane elastomer is an environmentally friendly material with simple synthesis and good performance. It has excellent high tension, high tensile force, strong toughness and aging resistance. It can be applied to yoga mats, but the antibacterial performance of thermoplastic polyurethane elastomer is not good. Therefore, its antibacterial performance needs to be improved. Although the wear resistance of thermoplastic polyurethane elastomer is good, its wear resistance cannot meet the use of yoga mats. Therefore, the wear resistance also needs to be improved.

[0004] Citronellol is a non-cyclic monoterpene alcohol with a rose scent and a wide range of pharmacological activities, such as antibacterial, anti-allergic, and anti-inflammatory. It is now widely used in cosmetics, household cleaners and other fields. However, citronellol is volatile, which limits its further application. Therefore, this defect needs to be overcome so that it can be more widely used. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a wear-resistant and antibacterial TPE composite material and its application in a yoga mat.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] The wear-resistant and antibacterial TPE composite material comprises the following raw materials, measured by weight: 100 parts of thermoplastic polyurethane elastomer and 1-5 parts of citronella-based carbon nanotubes;

[0008] Furthermore, the wear-resistant and antibacterial TPE composite material is prepared by the following steps:

[0009] The dried thermoplastic polyurethane elastomer and citronella-based carbon nanotubes are added into an internal mixer for melt blending to obtain a blend, and then the blend is transferred into a pulverizer for granulation, and finally placed in an injection molding machine for injection molding to obtain a wear-resistant and antibacterial TPE composite material.

[0010] Furthermore, in the melt blending, the blending temperature is set to 180-200° C., the rotation speed is set to 50 r / min, and the time is set to 15-20 min.

[0011] Furthermore, the injection pressure is 120 MPa, the injection time is 5 s, the holding time is 10 s, and the temperatures in the heating section are 210°C, 200°C, 195°C, and 190°C.

[0012] Furthermore, the citronella-based carbon nanotubes are prepared by the following steps:

[0013] (1) Weigh maleic acid in a dry flask, add thionyl chloride, control the reflux temperature to 75-80°C, react for 2-5 hours, and after the reaction is completed, distill under reduced pressure, cool to room temperature, and dry to obtain maleic acid chloride; the dosage ratio of maleic acid to thionyl chloride is 1g: (8-14)mL;

[0014] Maleic acid and thionyl chloride undergo chlorination reaction to obtain maleic acid chloride. The reaction process is as follows:

[0015] ;

[0016] (2) In a nitrogen atmosphere, citronellol and triethylamine are added to a flask containing dichloromethane, and the mixture is stirred to dissolve. Maleic acid chloride is added thereto at 0-5°C, and the mixture is stirred to disperse. The mixture is heated to 20-30°C and reacted for 6-12 hours. After the reaction is completed, the mixture is filtered under reduced pressure, and the filtrate is concentrated by rotary evaporation, extracted, and dried to obtain citronellol maleate. The dosage ratio of citronellol, triethylamine, and maleic acid chloride is (2-2.4) g: (1.4-1.6) g: 1 g. Under the action of triethylamine, the -OH on the citronellol molecule undergoes an esterification reaction with maleic acid chloride to obtain citronellol maleate. The reaction process is shown below:

[0017] ;

[0018] (3) Weigh citronellyl maleate and add it to a flask, add tetrahydrofuran thereto, stir and disperse, then add a tetrahydrofuran solution of furanyl methylamine thereto, stir and mix evenly, add anhydrous aluminum chloride as a catalyst, control the temperature to 70-85°C, react for 10-16 hours, and after the reaction is completed, rotary evaporate and dry to obtain bis-citronellyl furanyl methylamine; the dosage ratio of citronellyl maleate, furanyl methylamine and anhydrous aluminum chloride is 1g: (0.25-0.3)g: (0.01-0.03)g; under the catalytic action of anhydrous aluminum chloride, citronellyl maleate and furanyl methylamine undergo a Diels-Alder reaction to synthesize bis-citronellyl furanyl methylamine, and the reaction process is as follows:

[0019] ;

[0020] (4) Weigh bis-citronellyl furan methylamine and add it to a flask, add ethanol to it, stir and disperse it, then add acidified carbon nanotubes to it, and ultrasonically disperse it for 1-3 hours. After the end, remove the solvent by rotary evaporation and dry it to obtain citronellyl carbon nanotubes; the amount ratio of bis-citronellyl furan methylamine to acidified carbon nanotubes is (0.2-0.4) g:1 g; use the carboxyl groups on the acidified carbon nanotubes to react with bis-citronellyl furan methylamine to obtain citronellyl carbon nanotubes. The reaction process is as follows:

[0021] ;

[0022] Another object of the present invention is to provide application of the wear-resistant and antibacterial TPE composite material of the present invention in a yoga mat.

[0023] Beneficial effects of the present invention:

[0024] (1) The carbon nanotubes used in the present invention are prone to agglomeration and uneven dispersion in the polymer matrix during the blending process due to the surface effect and van der Waals interaction force. The present invention functionalizes the carbon nanotubes, i.e., reacts the carbon nanotubes with bis-citronellyl furan methylamine to improve the compatibility of the carbon nanotubes with the polymer, thereby improving the dispersion performance of the carbon nanotubes in the thermoplastic polyurethane elastomer. After processing, the carbon nanotubes are tightly combined with the matrix material and are difficult to separate from the matrix. The debris ground out during the sliding friction process can form a thin film with good lubrication performance, thereby reducing the loss during the friction process and improving the wear resistance of the TPE composite material.

[0025] (2) The citronellol used in the present invention is volatile. The present invention conducts an esterification reaction between the citronellol and maleic acid chloride, and then undergoes a series of reactions to obtain citronellol carbon nanotubes, thereby reducing the volatility of the citronellol, improving the utilization rate, and improving the antibacterial stability. The citronellol is then blended with a thermoplastic polyurethane elastomer to further improve the antibacterial properties of the TPE composite material.

[0026] (3) The present invention synthesizes bis-citronellyl furanamine by using citronellyl maleate and furanamine to undergo Diels-Alder reaction, and then obtains citronellyl carbon nanotubes through a series of reactions, which contain a DA cross-linked network structure. When the surface of the material is damaged and cracks are generated, the material can be treated by heat, infrared, or microwaves to transmit energy to the inside of the material, so that the DA cross-linked network obtains energy and breaks. The macromolecules cross-linked by DA bonds can undergo thermal motion and reorganization, so that the cracks are gradually repaired. When the external energy disappears, the DA cross-linked network is reorganized, and the performance of the material is restored. The material is blended with a thermoplastic polyurethane elastomer to improve the self-healing performance of the thermoplastic polyurethane elastomer. The thermoplastic polyurethane elastomer prepared by the present invention has been confirmed to have excellent antibacterial properties, wear resistance, and self-healing properties. The wear-resistant and antibacterial TPE composite material prepared by the present invention has very important application value in yoga mats. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] The preparation of acidified carbon nanotubes was carried out as follows: 0.5 g of carbon nanotubes was added to a mixed solution of 200 mL of sulfuric acid and nitric acid, the volume ratio of sulfuric acid to nitric acid was 3:1, ultrasonic stirring was performed for 1 h, deionized water was diluted, suction filtered, and deionized water was washed to pH 7, and dried to obtain acidified carbon nanotubes. Embodiment 1

[0029] (1) Weigh 5.8 g of maleic acid into a dry flask, add 46.4 mL of thionyl chloride, control the reflux temperature to 80°C, react for 4 h, and after the reaction is completed, distill under reduced pressure, cool to room temperature, and dry to obtain maleic acid chloride.

[0030] (2) In a nitrogen atmosphere, 17 g of citronellol and 11 g of triethylamine were added to a flask containing dichloromethane and stirred to dissolve. At 5°C, 7.6 g of maleic acid chloride was added thereto and stirred to disperse. The temperature was raised to 25°C and the reaction was carried out for 12 h. After the reaction was completed, the filtrate was filtered under reduced pressure and concentrated by rotary evaporation. The filtrate was extracted and dried to obtain citronellol maleate.

[0031] (3) Weigh 10 g of citronellyl maleate into a flask, add tetrahydrofuran thereto, stir and disperse, then add a tetrahydrofuran solution containing 2.5 g of furanyl methylamine thereto, stir and mix evenly, add 0.2 g of anhydrous aluminum chloride as a catalyst, control the temperature to 85°C, react for 16 h, and after the reaction is completed, rotary evaporate and dry to obtain bis-citronellyl furanyl methylamine.

[0032] (4) Weigh 2 g of bis-citronellyl furanamine and add it to a flask. Add ethanol and stir to disperse it. Then add 10 g of acidified carbon nanotubes and disperse it by ultrasonic. After dispersion for 3 h, remove the solvent by rotary evaporation and dry to obtain citronellyl carbon nanotubes.

[0033] (5) Add 20 g of dry thermoplastic polyurethane elastomer and 0.2 g of citronella-based carbon nanotubes into an internal mixer for melt blending. Set the blending temperature to 190 °C, the rotation speed to 50 r / min, and the time to 15 min to obtain a blend. Then transfer the blend to a grinder for granulation. Finally, place it in an injection molding machine for injection molding. Set the injection pressure to 120 MPa, the injection time to 5 s, the holding time to 10 s, and the temperatures in the heating section to 210 °C, 200 °C, 195 °C, and 190 °C to obtain a wear-resistant and antibacterial TPE composite material. Embodiment 2

[0034] (1) Weigh 5.8 g of maleic acid into a dry flask, add 81.2 mL of thionyl chloride, control the reflux temperature to 75 °C, react for 5 h, and after the reaction is completed, distill under reduced pressure, cool to room temperature, and dry to obtain maleic acid chloride.

[0035] (2) In a nitrogen atmosphere, 16 g of citronellol and 12 g of triethylamine were added to a flask containing dichloromethane and stirred to dissolve. At 0°C, 7.6 g of maleic acid chloride was added thereto and stirred to disperse. The temperature was raised to 25°C and the reaction was carried out for 8 h. After the reaction was completed, the filtrate was filtered under reduced pressure and concentrated by rotary evaporation. The filtrate was extracted and dried to obtain citronellol maleate.

[0036] (3) Weigh 10 g of citronellyl maleate into a flask, add tetrahydrofuran thereto, stir and disperse, then add a tetrahydrofuran solution containing 2.6 g of furanyl methylamine thereto, stir and mix evenly, add 0.3 g of anhydrous aluminum chloride as a catalyst, control the temperature to 75°C, react for 16 h, and after the reaction is completed, rotary evaporate and dry to obtain bis-citronellyl furanyl methylamine.

[0037] (4) Weigh 2 g of bis-citronellyl furan methylamine and add it to a flask, add ethanol, stir and disperse, then add 10 g of acidified carbon nanotubes and disperse by ultrasonic for 2 h. After the dispersion is completed, remove the solvent by rotary evaporation and dry to obtain citronellyl carbon nanotubes.

[0038] (5) Add 20 g of dried thermoplastic polyurethane elastomer and 0.4 g of citronella-based carbon nanotubes into an internal mixer for melt blending. Set the blending temperature to 200 °C, the rotation speed to 50 r / min, and the time to 16 min to obtain a blend. Then transfer the blend to a grinder for granulation. Finally, place it in an injection molding machine for injection molding. Set the injection pressure to 120 MPa, the injection time to 5 s, the holding time to 10 s, and the temperatures in the heating section to 210 °C, 200 °C, 195 °C, and 190 °C to obtain a wear-resistant and antibacterial TPE composite material. Embodiment 3

[0039] (1) Weigh 5.8 g of maleic acid into a dry flask, add 60 mL of thionyl chloride, control the reflux temperature to 80 °C, react for 2 h, and after the reaction is completed, distill under reduced pressure, cool to room temperature, and dry to obtain maleic acid chloride.

[0040] (2) In a nitrogen atmosphere, 15.2 g of citronellol and 10.6 g of triethylamine were added to a flask containing dichloromethane and stirred to dissolve. At 0°C, 7.6 g of maleic acid chloride was added thereto and stirred to disperse. The temperature was raised to 25°C and the reaction was carried out for 12 h. After the reaction was completed, the filtrate was filtered under reduced pressure and concentrated by rotary evaporation. The filtrate was extracted and dried to obtain citronellol maleate.

[0041] (3) Weigh 10 g of citronellyl maleate into a flask, add tetrahydrofuran thereto, stir and disperse, then add a tetrahydrofuran solution containing 3 g of furanyl methylamine thereto, stir and mix evenly, add 0.1 g of anhydrous aluminum chloride as a catalyst, control the temperature to 70°C, react for 10 h, and after the reaction is completed, rotary evaporate and dry to obtain bis-citronellyl furanyl methylamine.

[0042] (4) Weigh 4 g of bis-citronellyl furan methylamine and add it to a flask, add ethanol, stir and disperse it, then add 10 g of acidified carbon nanotubes and disperse it by ultrasonication for 1 hour. After the dispersion is completed, remove the solvent by rotary evaporation and dry to obtain citronellyl carbon nanotubes.

[0043] (5) Add 20 g of dried thermoplastic polyurethane elastomer and 0.6 g of citronella-based carbon nanotubes into an internal mixer for melt blending. Set the blending temperature to 180 °C, the rotation speed to 50 r / min, and the time to 20 min to obtain a blend. Then transfer the blend to a grinder for granulation. Finally, place it in an injection molding machine for injection molding. Set the injection pressure to 120 MPa, the injection time to 5 s, the holding time to 10 s, and the temperatures in the heating section to 210 °C, 200 °C, 195 °C, and 190 °C to obtain a wear-resistant and antibacterial TPE composite material. Embodiment 4

[0044] (1) Weigh 5.8 g of maleic acid into a dry flask, add 80 mL of thionyl chloride, control the reflux temperature to 80 °C, react for 4 h, and after the reaction is completed, distill under reduced pressure, cool to room temperature, and dry to obtain maleic acid chloride.

[0045] (2) In a flask filled with dichloromethane under a nitrogen atmosphere, add 16 g of citronellol and 12.2 g of triethylamine, stir to dissolve, add 7.6 g of maleic acid chloride at 5°C, stir to disperse, raise the temperature to 30°C, react for 6 h, and after the reaction is completed, filter under reduced pressure, concentrate the filtrate by rotary evaporation, extract, and dry to obtain citronellol maleate.

[0046] (3) Weigh 10 g of citronellyl maleate into a flask, add tetrahydrofuran thereto, stir and disperse, then add a tetrahydrofuran solution containing 2.5 g of furanyl methylamine thereto, stir and mix evenly, add 0.2 g of anhydrous aluminum chloride as a catalyst, control the temperature to 85°C, react for 12 h, and after the reaction is completed, rotary evaporate and dry to obtain bis-citronellyl furanyl methylamine.

[0047] (4) Weigh 3 g of bis-citronellyl furan methylamine and add it to a flask, add ethanol, stir and disperse, then add 10 g of acidified carbon nanotubes and disperse by ultrasonic for 2 h. After the dispersion is completed, remove the solvent by rotary evaporation and dry to obtain citronellyl carbon nanotubes.

[0048] (5) Add 20 g of dried thermoplastic polyurethane elastomer and 0.8 g of citronella-based carbon nanotubes into an internal mixer for melt blending. Set the blending temperature to 190 °C, the rotation speed to 50 r / min, and the time to 15 min to obtain a blend. Then transfer the blend to a grinder for granulation. Finally, place it in an injection molding machine for injection molding. Set the injection pressure to 120 MPa, the injection time to 5 s, the holding time to 10 s, and the temperatures in the heating section to 210 °C, 200 °C, 195 °C, and 190 °C to obtain a wear-resistant and antibacterial TPE composite material. Embodiment 5

[0049] (1) Weigh 5.8 g of maleic acid into a dry flask, add 50 mL of thionyl chloride, control the reflux temperature to 80 °C, react for 4 h, and after the reaction is completed, distill under reduced pressure, cool to room temperature, and dry to obtain maleic acid chloride.

[0050] (2) In a nitrogen atmosphere, 18.2 g of citronellol and 11 g of triethylamine were added to a flask containing dichloromethane and stirred to dissolve. At 5°C, 7.6 g of maleic acid chloride was added thereto and stirred to disperse. The temperature was raised to 20°C and the reaction was carried out for 10 h. After the reaction was completed, the filtrate was filtered under reduced pressure and concentrated by rotary evaporation. The filtrate was extracted and dried to obtain citronellol maleate.

[0051] (3) Weigh 10 g of citronellyl maleate into a flask, add tetrahydrofuran thereto, stir and disperse, then add a tetrahydrofuran solution containing 2.8 g of furanyl methylamine thereto, stir and mix evenly, add 0.2 g of anhydrous aluminum chloride as a catalyst, control the temperature to 75°C, react for 14 h, and after the reaction is completed, rotary evaporate and dry to obtain bis-citronellyl furanyl methylamine.

[0052] (4) Weigh 3 g of bis-citronellyl furan methylamine and add it to a flask, add ethanol, stir and disperse, then add 10 g of acidified carbon nanotubes and disperse by ultrasonic for 2 h. After the dispersion is completed, remove the solvent by rotary evaporation and dry to obtain citronellyl carbon nanotubes.

[0053] (5) Add 20 g of dry thermoplastic polyurethane elastomer and 1 g of citronella-based carbon nanotubes into an internal mixer for melt blending. Set the blending temperature to 200 °C, the rotation speed to 50 r / min, and the time to 20 min to obtain a blend. Then transfer the blend to a grinder for granulation. Finally, place it in an injection molding machine for injection molding. Set the injection pressure to 120 MPa, the injection time to 5 s, the holding time to 10 s, and the temperatures in the heating section to 210 °C, 200 °C, 195 °C, and 190 °C to obtain a wear-resistant and antibacterial TPE composite material.

[0054] Comparative Example 1

[0055] The preparation method of the wear-resistant and antibacterial TPE composite material provided in this comparative example is substantially the same as that in Example 1, the main difference is that in Comparative Example 1, the citronella-based carbon nanotubes in Example 1 are replaced with carbon nanotubes.

[0056] Comparative Example 2

[0057] The preparation method of the wear-resistant and antibacterial TPE composite material provided in this comparative example is substantially the same as that in Example 1, the main difference being that in Comparative Example 2, the citronella-based carbon nanotubes in Example 1 are replaced with citronellol.

[0058] Wear resistance test: Place a sample with a diameter of 15mm and a thickness of 8mm on a multifunctional friction and wear testing machine, and use a steel ball to rub the sample. The experimental speed is 200r / min, the load force is 10N, and the sample is weighed before the experiment as m1 and after the test as m2. The loss (g) = m1-m2.

[0059] Table 1:

[0060]

[0061] The smaller the loss, the better the wear resistance. It can be seen from the data in the above table that the TPE composite material prepared by the present invention has excellent wear resistance. Combined with the data of Comparative Example 1, it can be seen that the carbon nanotubes can enhance the interaction with the thermoplastic polyurethane elastomer after treatment, thereby improving the wear resistance of the TPE composite material.

[0062] Antibacterial performance test: On a clean workbench, use a sterile cotton swab to scrape Staphylococcus aureus and Candida albicans and place them in a sodium chloride-peptone buffer solution with a pH of 7. Use a sterile cotton swab to dip into a solution with a concentration of 6×10 6 cfu / mL of bacterial suspension was evenly spread on the surface of tryptic soy peptone agar medium plate, covered the plate, and left to dry at room temperature for 5 min. A sample with a diameter of 5 mm was placed on the stained plate in the center of the plate, covered the plate, and cultured in an incubator at 32°C for 24 h. The diameter of the inhibition ring was measured with a vernier caliper.

[0063] Table 2:

[0064]

[0065] The larger the diameter of the antibacterial ring, the better the antibacterial performance. It can be seen from the data in the above table that the TPE composite material prepared by the present invention has excellent antibacterial performance. Combined with the data of Comparative Example 2, it can be seen that after treatment, citronellol can reduce its volatility, enhance its antibacterial stability, and improve the antibacterial performance of the TPE composite material.

[0066] Self-healing performance test: refer to GB / T528-2009, use a universal testing machine to test the tensile performance, use a knife to scratch a 0.5mm scratch on the surface of the sample, place the sample in a constant temperature oven at 130℃ for 10min, then cool it to 60℃ and heat treat it for 12h, use the universal testing machine to stretch the sample again, and calculate the repair efficiency, repair efficiency (%) = (tensile strength of the sample after repair / tensile strength of the sample before repair) × 100%.

[0067] Table 3:

[0068]

[0069] It can be seen from the table that the TPE composite material prepared by the present invention has excellent self-repairing performance.

[0070] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A wear-resistant and antibacterial TPE composite material, characterized in that: The following raw materials are included in parts by weight: 100 parts of thermoplastic polyurethane elastomer, 1-5 parts of citronella-based carbon nanotubes; The wear-resistant and antibacterial TPE composite material is prepared by the following steps: The dried thermoplastic polyurethane elastomer and citronella-based carbon nanotubes are added into an internal mixer for melt blending to obtain a blend, and then the blend is transferred into a pulverizer for granulation, and finally placed in an injection molding machine for injection molding to obtain a wear-resistant and antibacterial TPE composite material. The citronella-based carbon nanotubes are prepared by the following steps: (1) Weigh maleic acid in a dry flask, add thionyl chloride thereto, control the reflux temperature to 75-80° C., react for 2-5 hours, and after the reaction is completed, distill under reduced pressure, cool to room temperature, and dry to obtain maleic acid chloride; (2) In a nitrogen atmosphere, citronellol and triethylamine are added to a flask containing dichloromethane, and the mixture is stirred to dissolve. Maleic acid chloride is added thereto at 0-5° C., and the mixture is stirred to disperse. The mixture is heated to 20-30° C., and the reaction is performed for 6-12 hours. After the reaction is completed, the mixture is filtered under reduced pressure, and the filtrate is concentrated by rotary evaporation, extracted, and dried to obtain citronellol maleate; (3) Weighing citronella maleate and adding it to a flask, adding tetrahydrofuran thereto, stirring and dispersing, then adding a tetrahydrofuran solution of furanyl methylamine thereto, stirring and mixing evenly, adding anhydrous aluminum chloride as a catalyst, controlling the temperature to 70-85° C., reacting for 10-16 hours, and after the reaction is completed, rotary evaporation and drying to obtain bis-citronella furanyl methylamine; (4) Weigh bis-citronellyl furanamine and add it to a flask, add ethanol, stir and disperse it, then add acidified carbon nanotubes, use the carboxyl groups on the acidified carbon nanotubes to react with bis-citronellyl furanamine for amidation, and ultrasonically disperse for 1-3 hours. After the reaction, remove the solvent by rotary evaporation and dry to obtain citronellyl carbon nanotubes.

2. The wear-resistant and antibacterial TPE composite material according to claim 1, characterized in that: In the melt blending, the blending temperature is set to 180-200° C., the rotation speed is set to 50 r / min, and the time is set to 15-20 min.

3. The wear-resistant and antibacterial TPE composite material according to claim 1, characterized in that: The injection pressure is 120 MPa, the injection time is 5 s, the holding time is 10 s, and the temperatures in the heating section are 210°C, 200°C, 195°C, and 190°C.

4. The wear-resistant and antibacterial TPE composite material according to claim 1, characterized in that: In the above (1), the usage ratio of maleic acid and thionyl chloride is 1 g:(8-14) mL.

5. The wear-resistant and antibacterial TPE composite material according to claim 1, characterized in that: In the above (2), the usage ratio of citronellol, triethylamine and maleic acid chloride is (2-2.4) g:(1.4-1.6) g:1 g.

6. The wear-resistant and antibacterial TPE composite material according to claim 1, characterized in that: In the above (3), the usage ratio of citronellyl maleate, furanyl methylamine and anhydrous aluminum chloride is 1g:(0.25-0.3)g:(0.01-0.03)g.

7. The wear-resistant and antibacterial TPE composite material according to claim 1, characterized in that: In the above (4), the usage ratio of bis-citronellyl furan methylamine and acidified carbon nanotubes is (0.2-0.4) g:1 g.

8. Application of the wear-resistant and antibacterial TPE composite material as claimed in claim 1 in a yoga mat.

Citation Information

Patent Citations

  • Filler for composite-material article

    TW201638206A

  • Self-healing polycarbonate containing polyurethane nanotube composite

    US8846801B1